URGENSI ILMU PENGETAHUAN DALAM ERA SOCIETY 5.0: SEBUAH PERSPEKTIF SEJARAH ISLAM - Yusril Fahmi Adam (Postgraduate State Islamic Institute (IAIN) Metro, 2022)
This article is a qualitative research that aims to analyze the urgency of science for Muslims in Indonesia in the era of society 5.0 from a historical perspective. In collecting data or sources, this research uses library research methods, namely by looking for data in the form of books, documents, and other sources such as journal articles related to the discussion theme. This research also uses a philosophical approach as an auxiliary science in the analysis. With the sources that have been obtained and the auxiliary science used, this research is not only narrative-descriptive, but rather analytical-descriptive. The results of this study are that Indonesian Muslims have great challenges and responsibilities to be involved in the development of science in the era of society 5.0. Historical reality has recorded that Muslims experienced a heyday in ancient Egypt and the Abbasid State, but current historical facts show that Muslims in Indonesia and even the world in general are not the drivers of scientific and technological progress in this era of society 5.0. With the emergence of a passion for studying, Indonesian Muslims are not only able to control, predict and develop knowledge, they can even create cutting-edge technology and can compete on an international scale.